MENINGKATKAN HASIL BELAJAR SISWA KELAS V SDN RENGEL IV MELALUI METODE OUTDOOR STUDY MATERI PESAWAT SEDERHANA - Sri Cacik; Wiwin Yuliana (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2016)
Based on observations in mind that science learning outcomes of fifth grade students at SDN Rengel IV is still low. It is caused by several factors, one of which is a learning process. In the process of learning a lot of students who do not pay attention to the teacher's explanations, the students motivation to learn is still low, and students are not involved in finding a concept. Therefore, the researcher applied the outdoor study method to solve the problem. The purpose of this study was to determine improving student learning outcomes and student response to the outdoor study method. This research is a Classroom Action Research (CAR) which each cycle consists of four phases: planning, action, observation, and reflection. Instruments used in the study were test sheet of learning outcome and questionnaire responses. The data of student learning outcomes was analyzed as the student classical completeness. The results showed that after learning by using outdoor study methode, the classical completeness of student increased from 42% to 86% and the students gave positive responses.